The stolen child : a novel [large type] - Hood, Ann, 1956- (Thorndike Press large print top shelf., 2024)
Haunted by a decision he made as a young soldier in World War I, involving a French artist and her baby, Nick Burns, with only months left to live, enlists Jenny, a college dropout, to help him unravel the mystery, forcing them both to reckon with regret, betrayal and the lives they've left behind.